A Self-Guiding Tool to Conduct Research With Embodiment Technologies Responsibly - Aymerich-Franch, Laura; Fosch-Villaronga, Eduard (Frontiers in Robotics and AI, 2020)
The extension of the sense of self to the avatar during experiences of avatar embodiment requires thorough ethical and legal consideration, especially in light of potential scenarios involving physical or psychological harm caused to, or by, embodied avatars. We provide researchers and developers working in the field of virtual and robot embodiment technologies with a self-guidance tool based on the principles of Responsible Research and Innovation (RRI). This tool will help them engage in ethical and responsible research and innovation in the area of embodiment technologies in a way that guarantees all the rights of the embodied users and their interactors, including safety, privacy, autonomy, and dignity.